Impact of admission type on students' achievement in economy and business school of Batusangkar State Institute of Islamic Studies - David, David; Guspendri, Nasvizar (Jurnal Penelitian dan Evaluasi Pendidikan, 2018)
The study is aimed at finding the differences in students' academic achievement based on the admission system type to IAIN Batusangkar and the size of the contribution of admission systems to students' achievement. The study uses the quantitative research approach. The comparative multivariate technique is used for the data analysis. Subjects include 159 student candidates for the local-exam stream, 161 for the national-exam stream, and 123 for the achievement-based stream. Findings show that there is a significant difference in academic achievement between students admitted through the achievement stream and students admitted through the local and national-exam streams. There is no significant difference between the local-exam system and the national-exam system. The contribution of admission systems over academic achievement is 5.4%; specified: 5.2% for Semester I, 2.3% for Semester II, 3.8% for Semester III, 4.1% for Semester IV, and 4.4% for Semester V.